The Role Of Psychological Capital Mediation On The Influence Of Auditor Experience On Audit Dysfunctional Behavior - Lismawati; Nila Aprilla; Riski Tri Septianita (UNIB Press, 2024)
This study aims to provide evidence of the effect of auditor experience on psychological capital, provide evidence of the effect of psychological capital on dysfunctional audit behaviour and provide evidence of the mediating effect of psychological capital on the effect of auditor experience on audit dysfunctional behaviour. This research includes quantitative descriptive research. Data collection in this study was carried out by distributing questionnaires to respondents online. The research respondents were internal auditors in Bengkulu Province. The number of auditors who became research respondents was 175 people, spread across 11 Inspectorate Offices in Bengkulu Province. The analysis method uses descriptive analysis and partial least square (PLS) analysis. The results showed that: (1) Auditor experience has a positive and significant influence on the psychological capital of auditors of the Inspectorate Office in Bengkulu Province; (2 Auditor psychological capital has a negative and significant influence on the dysfunctional behaviour of auditors of the Inspectorate Office in Bengkulu Province; and (3) Psychological capital has a mediating role in the effect of auditor experience on the dysfunctional behaviour of auditors of the Inspectorate Office in Bengkulu Province. Themediating role that occurs is partially mediation